Human endogenous retroviruslike genome with type C pol sequences and gag sequences related to human T-cell lymphotropic viruses. - Mager, D L (1987)
We have cloned several prototypic members of the family of human endogenous retroviruslike elements having a histidine tRNA primer-binding site (RTVL-H) and have determined the nucleotide sequence of one of these clones (RTVL-H2). The RTVL-H2 sequence is 5,813 nucleotides long, with long terminal repeats of 450 nucleotides. Although this particular sequence contains no long open reading frames, computer searches have revealed several segments of amino acid homology with known retroviral gene products. In the gag region of RTVL-H2, there is a segment with significant homology to a region of the gag protein p30 of type C baboon endogenous virus. In the pol region of RTVL-H2, three segments similar to the Moloney leukemia virus (MLV) pol polyprotein were detected. These correspond to parts of the protease, reverse transcriptase, and endonuclease domains of the MLV pol gene. Interestingly, the last two pol domains are equidistant in RTVL-H2 and the type C murine retroviruslike DNA sequence (MuRRS), both having deletions of equal sizes relative to the MLV pol gene. One other segment similar to a retroviral gene product was identified in the RTVL-H2 gag region. This segment has 55 to 60% amino acid homology to a 50-amino-acid region of the gag nucleic acid-binding proteins encoded by human T-cell lymphotropic viruses types I and II and bovine leukemia virus. Thus, the RTVL-H2 genome harbors sequences related to evolutionarily distant retroviruses.